Metabolic Complications in Liver Transplantation Recipients: How We Can Optimize Long‐Term Survival. Issue 10 (31st July 2021) - Azhie, Amirhossein; Sheth, Priya; Hammad, Ahmed; Woo, Minna; Bhat, Mamatha
Abstract : Liver transplantation (LT) recipients have experienced a significant improvement in short‐term survival during the past 3 decades attributed to advancements in surgical techniques, perioperative management, and effective immunosuppressive regimens. However, long‐term survival is affected by a high incidence of metabolic disorders and their consequences, including cardiovascular disease (CVD) and malignancies. Pretransplant metabolic impairments especially in those with nonalcoholic steatohepatitis cirrhosis are aggravated by the addition of posttransplant weight gain, physical inactivity, and reversal from catabolic to anabolic state. Moreover, although immunosuppressants are vital to avoid graft rejection, long‐term exposure to these medications is implicated in metabolic impairments after LT. In this review, we summarize the molecular pathogenesis of different metabolic disorders after LT, including diabetes mellitus, dyslipidemia, and nonalcoholic fatty liver disease. Furthermore, CVD, malignancies, and graft rejections were provided as significant complications of post‐LT metabolic conditions threatening both the patient and graft survival. Ultimately, emerging preventive and treatment strategies for posttransplant diabetes mellitus are summarized. This review highlights the significant need for more clinical trials of antihyperglycemic agents in LT recipients. Also, translational studies will help us to better understand the molecular and genetic factors underlying these metabolic complications and could lead to more personalized management in this high‐risk population. Abstract : https://wileyhealthlearning.com/#/online‐courses/294f284d‐5ec8‐4449‐a37a‐c7706e1b363d